Piperine, a functional food alkaloid, exhibits inhibitory potential against TNBS-induced colitis via the inhibition of IκB-α/NF-κB and induces tight junction protein (claudin-1, occludin, and ZO-1) signaling pathway in experimental mice. (April 2020) - Guo, G; Shi, F; Zhu, J; Shao, Y; Gong, W; Zhou, G; Wu, H; She, J; Shi, W
Background: Inflammatory bowel disease is a chronic immunoinflammatory disease of the gastrointestinal tract. Piperine, an alkaloid, has been reported to possess antioxidant, anti-inflammatory, antiapoptotic, and antiulcer potential. Aim: To elucidate the plausible mechanisms of action of piperine on experimental trinitrobenzenesufonic acid (TNBS)-induced colitis by assessing various biochemical, molecular, histological, and ultrastructural modifications. Methods: Colitis was induced in male Sprague–Dawley rats via intrarectal instillation of TNBS. Then, the rats were treated with piperine (10, 20, and 40 mg/kg, p.o.) for 14 days. Results: TNBS induced significant ( p < 0.05) colonic damage, which was assessed by disease activity index, macroscopic score, and stool consistency. The administration of piperine (20 and 40 mg/kg) significantly inhibited ( p < 0.05) these damages. Treatments with piperine (20 and 40 mg/kg) notably inhibited ( p < 0.05) the TNBS-induced elevation of oxido-nitrosative stress (superoxide dismutase, glutathione, malondialdehyde, and nitric oxide), 5-hydroxytryptamine, and hydroxyproline content in the colon. Furthermore, colonic inducible nitric oxide synthase (iNOs), tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β, IL-6, interferon-gamma, and cyclooxygenase-2 (COX-2) messenger RNA (mRNA) expressions were upregulated after TNBS instillation and piperine (20 and 40 mg/kg) significantly attenuated ( p < 0.05) these elevated mRNA expressions. TNBS decreased the expressions of tight junction (TJ) protein (claudin-1, occludin, and zonula occludens-1 (ZO-1)) and increased the expressions of proapoptotic (caspase-1) protein. These expressions were markedly inhibited ( p < 0.05) by piperine treatment. Histological and ultrastructural studies of transmission electron microscopy suggested that piperine significantly ameliorated ( p < 0.05) TNBS-induced colonic aberrations. Conclusion: Piperine ameliorated the progression of TNBS-induced colitis by modulating the nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor-alpha/nuclear factor-kappa B signaling pathway, thus inhibiting the overexpression of proinflammatory cytokines (TNF-α and IL's), COX-2, iNOs, oxido-nitrosative stress, and proapoptotic proteins (caspase-1) that may improve the expression of TJ protein (claudin-1, occludin, and ZO-1).